2017
DOI: 10.7860/jcdr/2017/27344.10514
|View full text |Cite
|
Sign up to set email alerts
|

Study of Red Cell Fragility in Different Stages of Chronic Kidney Disease in Relation to Parathyroid Hormone

Abstract: The underlying cause of anaemia should be identified early in the CKD patients before haemodialysis. Secondary hyperparathyroidism should be ruled out as a causative factor of anaemia to slow down the progression of the disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
2
4
0
1
Order By: Relevance
“…There was a significant reduction in hemoglobin levels with decreasing eGFR values as previously reported [ 46 ]. The primary cause of anemia is a reduction in EPO synthesis due to loss of renal functional mass [ 47 ].…”
Section: Discussionsupporting
confidence: 84%
“…There was a significant reduction in hemoglobin levels with decreasing eGFR values as previously reported [ 46 ]. The primary cause of anemia is a reduction in EPO synthesis due to loss of renal functional mass [ 47 ].…”
Section: Discussionsupporting
confidence: 84%
“…This confirms the shortened survival of RBC with the progression of renal dysfunction. This came in agrement with Panda et al who reported a statistically significant increase in the MOF with increasing the stage of CKD (0.35% ± 0.12%, 0.48% ± 0.11%, 0.62% ± 0.07% and 0.65% ± 0.66% in stage II, III A, III B and IV CKD respectively) [14]. In this study, there was a statistically significant string positive correlation between MOF and PTH levels (r = 0.836, P < 0.001*) (Table 4).…”
Section: Discussionsupporting
confidence: 54%
“…In the study conducted by Panda and his colleagues, ROC analysis revealed an area under the curve of 0.980 with a sensitivity of 100% and specificity of 87% in detecting osmotic fragility at a cut-off value of PTH ≥ 100 pg/ml [14]. There is also a statistically significant positive correlation between MOF with Creatinine, Urea, Phosphorous, Ca*phosphorous product, K, KTV and PTH (Table 5).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In all the groups the fall of urea corresponds to the excess discharge of nitrogen, indicating the overwork of kidneys or load on kidneys plus disturbance in metabolism of nitrogen. This may relate to alteration in parathyroid hormone [33] by influence by atorvastatin. The fall may be due to nephrotoxic effect in this dose where inhibition of p38mitogen-activated protein kinase (MAPK), as well as nuclear factor kappa-β (NF-κβ) signaling pathways, and inducible nitric oxide synthase (NOS) expression is altered [34].…”
Section: Discussionmentioning
confidence: 99%